Exploring the role of supervisors in the psychological well-being of low-income working mothers - Syara Shazanna Zulkifli; Hazalizah Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study explored the experience of supervisor support and identified essential supervisor support from the perspective of Malaysian low-income working mothers. A semi-structured in-depth interview following the interpretive research design was utilized. A total of 9 participants were recruited through purposive sampling and were interviewed online or by a mobile phone. The raw audio was then meticulously transcribed by the researcher using intelligent verbatim. The data was analysed using framework analysis. Participants experienced a mix of supervisor support experiences, including negative experiences such as workplace incivility, harassment, and relational conflict with supervisors, as well as positive experiences including psychological reassurance and work optimization and management. In line with the experience, participants requested support that is tangible and psychological and favours a transformational leadership style. The findings of this study will help outline training for supervisors on responsibilities, workplace issues, and employee well-being, guide in the revision and implementation of workplace policies and provide opportunities to empower working mothers as well as other employees’ well-being through supervisor support within the context of the workplace.